Worker debt, default ans diversity of financial fragility - Matthieu Charpe; Peter Flaschel (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
This paper presents a model addressing the conditions under which financial instability arises in the event of household debt. The model addresses two main cases. First, household debt is affected by functional income distribution. Second, household debt is affected by credit supply and depends on bank performances. The model shows that financial fragility arises through a Fisher effect in the first case and through a debt financed consumption boom in the second case. The model then explores two extensions. First, we raise the question of debt default and its impact on financial instability. Second, we discuss the ability of capital adequacy ratio to limit financial instability.
urn:nbn:de:101:1-201202285198
Keywords: E3; E6; H1; 330; Flexicurity; employer of rst resort; Solovian growth; company pension funds; sustainability; Private Verschuldung; Finanzkrise; Bankenkrise; Fisher-Effekt; Verbraucherkredit; Theorie